Would cat owners intend to treat their cats if diagnosed with heart disease? - Kuan, Hua Khor; Kuan, Siew Khor; Yong, Chong Lee; Yi, Jun Lim (Elsevier, 2021)
Heart disease is a prevalent medical condition among cats. The effectiveness of monitoring the cat's health condition, especially for those cats that may have underlying heart disease, may be dependent on their owner's ability to detect concerns that may signal clinical heart disease and making the effort to take the cat to the veterinarian to establish the correct diagnosis. After having been informed of their cats’ heart condition, the owner's decision to seek treatment may be dependent on the suggested treatment regime and willingness to manage the cat on lifelong therapy. Based on the theory of planned behavior, this study administered an interviewer-assisted survey to 139 respondents to examine cat owners' awareness and knowledge toward feline heart diseases, as well as perceived behavioral control as predictors to owners' intention to seek treatment for their cats. Sixty-nine respondents (49.6%) were aware that cats are susceptible to heart disease, of which forty-six respondents (66.7%) identified at least five signs of heart disease. While cost- and time-related reasons topped the list on barriers to owners in seeking treatment, fewer than half of the owners indicated that they would not find it troublesome to commit to the lifelong treatment regime. Based on the theory of planned behavior, attitude, subjective norm, and perceived behavioral control of cat owners are significant predictors to intention to treat cats with heart disease. Results also suggested that perceived behavioral control positively affected intention to seek treatments, especially among respondents who scored lower on empathic concern. Aside from the need for continuous educational interventions to improve cat owners' awareness and knowledge about feline heart disease, this study highlights the role of the veterinarian in encouraging treatment compliance for cats diagnosed with heart disease requiring lifelong therapy.